Histopathological changes in pregnant mice's hepar and kidney following exposure to kelor (Moringa oleifera) leaf extract - Armalina, Desy; Susilaningsih, Neni; Saraswati, Indah (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2025)
Background: Moringa provides extra dietary benefits. The immune system is significantly influenced by the nine necessary amino acids, calcium, iron, potassium, magnesium, zinc, and vitamins A, C, E, and B that are included in this food. Previous studies state that moringa causes liver and kidney damage. Another study found that moringa has an abortive effect.Objectives: This study aimed to determine how exposure to kelor (moringa oleifera) leaf extract affected the hepar and kidney in pregnant mice and found the secondary metabolite of the moringa leaves.Materials and Methods: An experimental laboratory design was conducted in 24 pregnant female Balb/c mice. They were randomized into four groups. Group K was not given anything. Group P1-P3 were given moringa leaf extract during pregnancy at days with a dose dose of 10, 20, and 30 mg in 10, 20, and 18 days, and termination was done to take the organs and make the tissue processing.Results: We found no dead mice and no aggression during the experiment. Significant statistics differed between the experimental group in the microscopic appearance of the kidney and hepar. This study found degeneration and inflammation in the hepar and kidney in the treatment group. Qualitative phytochemical tests on leaves contained alkaloids, flavonoids, phenolics, tannins, and steroids.Conclusion: The ethanol extract of Moringa leaf has shown a mild heparin and kidney effect compared to the control.